Życie i dzieło Marcina Lutra a spór wokół tez i narodzin Reformacji - Wojciech Miedwid (Polonia Sacra)
The article concerns the life and work of Martin Luther and takes on the dispute over the 95 theses and the birth of the sixteenth-century Reformation. From the beginning, it was wearing the stigma experiences of the Founder. The Reformer experienced a deep concern in the area of spiritual life and he solved his dilemmas based on biblical theology, which led him to formulation of the 95 theses. The Theses didn’t cause a break with the Church, because their content wasn’t in conflict with the contemporary doctrine of the Church, however, then were formulated to harshly and sometimes they were exaggerated. He wanted to discuss and define better the matter of indulgences. The purpose of this article is to show that the teaching of M. Luther and his struggle with visible religious abuses didn’t have to end in a split in the Church, because the reform movement was meant to be a renewal of Christianity.